Peran Budaya Organisasi dalam Mempengaruhi Loyalitas Karyawan di Grand Rocky Hotel Kota Bukittinggi - Cindy Dameza Hendrix; Youmil Abrian (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This research was conducted because there are several phenomena in the form of employee displacement at Grand Rocky Hotel in Bukittinggi. Behind the high employee loyalty at Grand Rocky Hotel, there are still several employee complaints such as overtime work, and the high workload received by employees. The purpose of this study is to analyse how organisational culture affects employee loyalty at Grand Rocky Hotel Bukittinggi. The method used is a causal associative approach with a population of 106 employees and a sample determined by proportional sampling technique with a sample of 52 employees. The data collection technique used a questionnaire/questionnaire which was arranged according to a Likert scale. Data analysis uses linear regression analysis to see whether organisational culture has an influence on employee loyalty at Grand Rocky Hotel in bukittinggi.Based on the results of hypothesis testing that has been done, the R Square value is 0.124, meaning that the contribution of organizational culture variables to employee loyalty is 12.4% while 87.6% is influenced by other factors. Organizational culture has a positive effect on employee loyalty with a coeffitient value of 0.352, meaning that organizational culture plays a role or has an effect on increasing employee loyalty.